2020
DOI: 10.1002/pon.5469
|View full text |Cite
|
Sign up to set email alerts
|

Trend of depression and its association with sociodemographic and clinical factors among multiple myeloma hospitalizations: A Portuguese nationwide study from 2000 to 2015

Abstract: Objective: Patients hospitalized with multiple myeloma (MM) are particularly vulnerable to depression. The present study aims to determine the frequency of depression among MM hospitalized patients, in order to assess the possible differences between those with and without depression in relation to sociodemographic and clinical variables and to measure the impact of depression on hospitalization outcomes. Methods: An observational retrospective study was performed using an administrative data set of all hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…In our study, obese MM patients did not have a statistically increased risk of mortality; this is in contradiction to a previous meta-analysis that noted that obesity is associated with a higher relative risk of death [36]. A large Portuguese study has shown the odds of in-hospital mortality are lower in depressed patients, but the length of hospital stay is longer [37]. Similarly, in real-world data, overall survival from chronic obstructive pulmonary disease (COPD) in multiple myeloma is worse, which contradicts our finding of a low odds ratio of mortality in hospitalized patients [38,39].…”
Section: Predictors Of Aprdrg Disabilitycontrasting
confidence: 99%
“…In our study, obese MM patients did not have a statistically increased risk of mortality; this is in contradiction to a previous meta-analysis that noted that obesity is associated with a higher relative risk of death [36]. A large Portuguese study has shown the odds of in-hospital mortality are lower in depressed patients, but the length of hospital stay is longer [37]. Similarly, in real-world data, overall survival from chronic obstructive pulmonary disease (COPD) in multiple myeloma is worse, which contradicts our finding of a low odds ratio of mortality in hospitalized patients [38,39].…”
Section: Predictors Of Aprdrg Disabilitycontrasting
confidence: 99%
“…To date, only a few studies have assessed the depressive and anxious states of MM patients in the early survivorship period ( Ribeiro-Carvalho et al, 2020 ; Zaleta et al, 2020 ). Practitioners generally believe that the anxiety and depression should be eased after maintenance therapy.…”
Section: Discussionmentioning
confidence: 99%